AniFOUND: analysing the associated proteome and genomic landscape of the repaired nascent non-replicative chromatin. Issue 11 (8th March 2021) - Stefos, Georgios C; Szantai, Eszter; Konstantopoulos, Dimitris; Samiotaki, Martina; Fousteri, Maria
Abstract: Specific capture of chromatin fractions with distinct and well-defined features has emerged as both challenging and a key strategy towards a comprehensive understanding of genome biology. In this context, we developed aniFOUND (accelerated native isolation of factors on unscheduled nascent DNA), an antibody-free method, which can label, capture, map and characterise nascent chromatin fragments that are synthesized in response to specific cues outside S-phase. We used the 'unscheduled' DNA synthesis (UDS) that takes place during the repair of UV-induced DNA lesions and coupled the captured chromatin to high-throughput analytical technologies. By mass-spectrometry we identified several factors with no previously known role in UVC-DNA damage response (DDR) as well as known DDR proteins. We experimentally validated the repair-dependent recruitment of the chromatin remodeller RSF1 and the cohesin-loader NIPBL at sites of UVC-induced photolesions. Developing aniFOUND-seq, a protocol for mapping UDS activity with high resolution, allowed us to monitor the landscape of UVC repair-synthesis events genome wide. We further resolved repair efficacy of the rather unexplored repeated genome, in particular rDNA and telomeres. In summary, aniFOUND delineates the proteome composition and genomic landscape of chromatin loci with specific features by integrating state-of-the-art 'omics' technologies to promote a comprehensive view of their function.